An investigation into linguistic expressions denoting “happiness” and “sadness” in english versus vietnamese literary works of vietnam war - Phạm,Thị Yên; Trần Quang Hải (ĐHĐN : ĐHĐN., 2015)
This study investigates linguistic expressions denoting “happiness” and “sadness” in literature works of Vietnam War in English versus Vietnamese. The study focuses on analyzing the semantic features and conceptual metaphors describing the two emotions. Metaphor in cognitive linguistic view not only is an important tool in human cognition and thought, but also plays a vital role in the conceptualization of emotion. This thesis is carried out to find out the similarities and differences in semantic features and conceptual metaphors used for describing “happiness” and “sadness” in English and Vietnamese literature works. More than 400 expressions describing “happiness” and “sadness” are collected in literary works in English and Vietnamese, from publication printings, and the Internet.
Master thesis in social scences and humanities.
Keywords: linguistic expressions denoting “happiness” and “sadness” in english versus vietnamese literary works of vietnam war; linguistic expressions denoting -- english versus